PENGUATAN PARTISIPASI MASYARAKAT DALAM PEMILAHAN SAMPAH DARI SUMBER DI KOTA BOGOR - Nanan Triyani (Bajang Institute, 2026)
The increasing volume of solid waste in Bogor City, reaching 291,154.77 tons per year in 2024, presents a serious challenge that cannot be addressed by the government alone. Although national regulations and local programs are in place, their implementation faces a fundamental gap as efforts to improve public literacy and behavioral change have not been carried out consistently or in a sustained manner. This policy paper aims to analyze the root causes of low community participation in waste reduction and source-separation, and to formulate concrete policy recommendations for the Bogor City Government, particularly the Department of Environment (Dinas Lingkungan Hidup). The analysis employs a qualitative approach using the USG (Urgency, Seriousness, Growth) method for priority problem determination, two-level root cause analysis, a review of community participation theory (Cohen and Uphoff, 1980), behavioral change theory (Theory of Planned Behavior, Ajzen 1991), the concept of waste banks and community empowerment, and an evaluation of three policy alternatives using the Bardach (2012) framework. The findings indicate that the priority problem is the low level of community participation in waste sorting at the source, rooted in waste management socialization that has not been conducted in a sustained and structured manner. Among the three alternatives evaluated, the comprehensive strengthening of the Waste-Free Neighborhood (RT Bebas Sampah) Program received the highest score (33), as it most effectively integrates education, institutional development, and infrastructure support simultaneously, while also enjoying strong political backing and a mechanism that has been tested in pilot areas. This paper recommends the enactment of a Mayor's Regulation (Peraturan Wali Kota) on the Strengthening of the RT Bebas Sampah Program, which mandates source-separated waste collection, the formation of neighborhood-level waste management teams, provision of sorting facilities, periodic community mentoring, and the phased establishment of Waste Bank Units across all neighborhoods (RT/RW) in Bogor City, supported by measurable performance indicators as a form of policy accountability.